Mechanical Properties of WC-Si3N4 Composites With Ultrafine Porous Boron Nitride Nanofiber Additive - Cao, Ting; Li, Xiaoqiang; Li, Jingmao; Huang, Yang; Qu, Shengguan; Yang, Chao; Liang, Liang; Song, Tao (Frontiers in Materials, 2021)
WC-10 wt.% Si3N4 composites toughened with ultrafine porous boron nitride nanofiber (0, 0.01, 0.05, 0.1, and 0.15 wt.%) were prepared for the first time by spark plasma sintering. Compared with the WC-Si3N4 composite sintered in the same condition, the obtained WC-10 wt.% Si3N4 composites with ultrafine porous boron nitride were found to possess better hardness and fracture toughness. In addition, the Si3N4 phase in the UPBNNF toughened composites did not exhibit traditional catastrophic fracture as indicated in most investigations. In this study, the phenomena are discussed, and a probable mechanism is elucidated. It is deduced that the approach could be extended to materials with a feature of internal liquid phase during the sintering process and could improve hardness and fracture toughness.